Migration, peasant communities and neoliberalism - Vegas Pozo, Jose (2009)
This assay is abouth the process of the rural communities in Canta, and mainly in downtown of Lima. I have a big interest to explore the economical, social, education factors that give big proportion to this test. There are 2 big social fenomenal that give the structure of this area: first, an intense privatization and concentration of the production factor; second, a great rural difference. The neoliberalism give this context sociocultural a difference. In the city, the migrants rebuilo the regional culture as an answer to the identity of the regional culture as an answer to the original cultural regional in the new condition of the original cultural and the new condition in the urban space. Processes that produce in a national level in different themes.